(untitled) (International Journal of Engineering and Computer Science, 2014)
MPLS-Traffic Engineering (MPLS-TE) provides various network recovery mechanisms such as rerouting and protection. In network routing algorithm is easily leading to the problem for some segments of a network are quite congested while other segments along alternative routes are underutilized. This thesis proposed a new route reconstruction approach wheeling and steering based route reconstruction approach in congested MPLS network. MPLS uses its routing technology to implement TE. This new algorithm is based on the advantages of MPLS. This is used to achieve load balancing of TE in MPLS network. The simulation of network is shown in NS2. The NS2 simulation showed that this approach can effectively balance the load between different links and improve the network performance with various perimeters as we can see in this paper in network communication simulation.